A Hard-to-Heal Cutaneous Ulcer: An Exuberant Case of Allergic Contact Dermatitis to L-Mesitran® Tulle - Calvão, Joana (2020)
L-Mesitran Tulle® is a popular non-adherent polyethylene dressing impregnated with the patented L-Mesitran Soft gel that contains Medilan™, which is said to be a “hypoallergenic lanolin”. Lanolin is a well know sensitizer and the prevalence of contact allergy to lanolin alcohols varies from 0.6% - 6.9%. We report the case of a patient who develop eczema around the leg ulcer while using L-Mesitran Tulle® as a wound dressing, highlighting that even this “high purity medical grade of lanolin” (Medilan™) contained in L-Mesitran Tulle® can cause an allergic contact dermatitis.